Water Pollution Shifts the Soil and Fish Gut Microbiomes Increasing the Circulation of Antibiotic Resistance Genes in the Environment - Magalhaes, Maithe Gaspar Pontes; Melo, Marilia Alves Figueira; Moreira, Aline dos Santos; Degrave, Wim; Parente, Thiago Estevam (Anais do Simpósio Brasileiro de Bioinformática (BSB); 2022: Anais do XV Simpósio Brasileiro de Bioinformática, 2022)
The impact of anthropogenic activities on urban rivers is responsible for changing the diversity and composition of aquatic species and microorganisms. In this study, soil and fish (Poecilia reticulata) feaces were sampled from two sites: the Cunha Canal, a heavily impacted urban river in Rio de Janeiro, and a reference clean site, to investigate how the Cunha Canal pollution impacts the microbiota composition and the circulation of antibiotic resistance genes (ARGs). In total, sequencing reads summed 3 million for the feaces and 9 million for the soil metagenomes. 67% of the soil and 83% of the fish feaces microbiota at both sites were classified as Bacteria. The soil microbiota of the reference site was enriched with bacteria of the genus Bradyrhizobium and Streptomyces known to fix nitrogen and to metabolize organic material, while the soil microbiota of Cunha Canal was enriched with Acidovorax and Dechloromonas known to degradate pollutants as iron and benzene. The five ARGs detected in the feaces microbiome from Cunha Canal are different from the five found in the feaces from the reference site. 22 ARGs were found in the soil sample of Cunha Canal, while no one was detected in the soil sample of the reference site. These results show that water pollution changes the microbiota diversity and increases the ARGs circulating in the environment.